Effectiveness of COVID-19 vaccination during pregnancy by circulating viral variantAJOG MFM at a Glance - Ousseny Zerbo, PhD; G. Thomas Ray, MBA; Bruce Fireman, MA; Evan Layefsky, BA; Kristin Goddard, MPH; Pat Ross, BA; Mara Greenberg, MD; Nicola P. Klein, MD, PhD (AJOG Global Reports, 2023)
BACKGROUND: SARS-CoV-2 infection in pregnancy can result in a spectrum of asymptomatic to critical COVID-19 outcomes, including hospitalization, admission to the intensive care unit, or death. OBJECTIVE: This study aimed to investigate the effectiveness of messenger RNA COVID-19 vaccination during pregnancy against both hospitalization and infection, stratified by different variant circulations and by time since the last vaccine dose. STUDY DESIGN: This was a retrospective cohort study among pregnant persons who were members of Kaiser Permanente Northern California and delivered between December 15, 2020, and September 30, 2022. Pregnant persons who received any vaccine dose before the pregnancy onset date were excluded. The primary outcome was hospitalization for COVID-19, and the secondary outcome was polymerase chain reaction–confirmed SARS-CoV-2 infection. Exposure was receipt of a messenger RNA vaccine during pregnancy. Poisson regression was used to estimate the risk ratio of hospitalization by comparing vaccinated pregnant persons with unvaccinated pregnant persons adjusted for sociodemographic factors and calendar time. Cox regression was used to estimate the hazard ratio of infection by comparing vaccinated pregnant persons with unvaccinated pregnant persons. Vaccine effectiveness was estimated as 1 minus the rate ratio or the hazard ratio multiplied by 100. Vaccine effectiveness was estimated overall and by variant periods (before Delta, Delta, Omicron, and subvariants). RESULTS: Of 57,688 pregnant persons, 16,153 (28%) received at least 1 dose of a messenger RNA COVID-19 vaccine during pregnancy; moreover, 4404 pregnant persons tested positive for SARS-CoV-2 infection, and 108 pregnant persons were hospitalized during pregnancy. Overall, 2-dose vaccine effectiveness against hospitalization was 91% within <150 days of vaccination and 48% >150 days after vaccination. The 2-dose vaccine effectiveness within <150 days after vaccination was 100% during the original virus strain and Delta variant periods of the virus; vaccine effectiveness was 51% during the Omicron period. Of the hospitalization cases, 97% of pregnant persons were unvaccinated. During hospitalization, none of the vaccinated pregnant persons required ventilation or were admitted to the intensive care unit. Moreover, 2-dose vaccine effectiveness against infection was 54% within <150 days after vaccination and 26% ≥150 days after vaccination. CONCLUSION: Messenger RNA COVID-19 vaccination during pregnancy was effective against hospitalization for COVID-19 and SARS-CoV-2 infection. COVID-19 was mild among pregnant persons who were vaccinated compared with those who were unvaccinated. Thus, all pregnant persons should be strongly encouraged to receive messenger RNA COVID-19 vaccines to prevent severe disease.